As santas de Zurbarán e a história da indumentária do século XVII - Navarro, Gisele Cristina (2020)
The Spanish baroque painter Francisco de Zurbarán (1598 - 1664) is known for his mastery of reproducing fabrics, and this skill reached the most notable point in his series of paintings of virgin martyr saints, which depicts sanctified characters of the Roman Empire and the Middle Ages with contemporary and luxurious outfits. This thematic and stylistic choice gives the viewer a glimpse of the clothes worn by the women who lived in the same period as the artist, with a wealth of details. However, more than simply documenting the fashion of the 17th century in these works, the artist included elements of clothing from the 16th century, prints and theatrical inspirations, and his own ways of combining and positioning the pieces of clothing, also acting as a fashion creator. The present study investigates these different aspects of Zurbarán, through bibliographic research and the analysis of 3 paintings - Santa Isabel de Portugal, Santa Casilda and Santa Margarita -, which provides a more detailed view of your knowledge about Spanish fashion, its creative process, its artistic and religious influences.